Magnetic Properties Analysis of Synthesis of Poly-(Vinyl Alcohol) / Clay / Nanomagnetite Composites: Application for Wastewater Filter - Benny Wahyudianto; Langit Cahya Adi (International Journal of Hydrological and Environmental for Sustainability, 2022)
The composites of poly–(vinyl alcohol) (PVA)/clay/Fe3O4 (magnetite) were synthesized with Fe(II) in-situ via hydrolysis method. The films were obtained as films by employing natural clay containing montmorrilonite (aluminosilicate) using casting technique. The weight variations of each component were also investigated. The resulting films were characterized with fourier transform infrared (FT-IR) to analyze their functional groups, and then X-ray diffractometer (XRD) was used to check the formation of magnetite and it was combined with Deybe-Scherrer equation to determine the theoretical size of magnetite. Along with that, vibrating sample magnetometer (VSM) analysis was carried out in order to measure the magnetic saturation brought by the magnetite inside composite system. FT-IR spectra showed peak around 610 cm-1and XRD diffracttogram pattern showed four characteristic peaks indicating (200); (311); and (511). Both results confirmed the formation of magnetite inside composite system. The result of VSM measurement showed that increasing PVA weight would lead into the decrease of the magnetic saturation of magnetite-contained composites due to hydroxyl group from PVA control its crystalline. Conversely, the reverse plot would be acquired if the precursor Fe(II)weight was augmented in the composite system due to another iron oxide species i.e.: goethite was predicted to form as the intermediate of magnetite. On the other hand, the amount variation of the aluminosilicate material was resulting no coherent plot through magnetic saturation value.